Increased Heparin Cofactor II Levels in Women Taking Oral Contraceptives - Toulon, P; Bardin, J M; Blumenfeld, N M (Thrombosis and Haemostasis, 1990)
Heparin cofactor II (HCII) is a thrombin inhibitor present in human plasma whose activity is enhanced by heparin. HCII exhibits important homologies with antithrombin III, the main heparin-enhanced thrombin inhibitor. Cases of recurrent thromboembolism have been recently reported in patients with HCII deficiency. Since the use of oral contraceptives (OC) is associated with an increased risk of thrombosis, the study of the plasma levels of HCII was undertaken in women taking contraceptive pills. Plasma HCII levels were found significantly higher in 62 women taking low-estrogen content OC (1.20 ± 0.28 U/ml) than in 62 age matched women not taking OC (0.94 ± 0.16 U/ml) or in 62 men (0.96 ± 0.19 U/ml). Significant correlations between HCII and fibrinogen levels were reported in the three groups. From the pooled data of the two control groups (men and women not taking OC), the normal range for plasma HCII levels was defined to be between 0.60 and 1.30 U/ml (mean ± 2 SD). Two cases of low HCII levels (<0.60 U/ml) were found in the control groups, but none in the group of women taking OC. It is concluded that the use of oral contraceptives is associated with a rise in HCII levels and that the screening for HCII deficiency has to be performed at distance of any OC therapy.